2020
DOI: 10.46223/hcmcoujs.soci.en.10.2.553.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of using cartoons as an instructional tool on English communicative skills of young learners at a Vietnamese primary school

Abstract: This study examined the impact of the use of cartoons on the speaking and listening skills of students in a primary school in a rural area in Vietnam and their attitudes towards the use of cartoons as a learning tool in their English classes. The study employed an experimental research design to collect data. Participants included 70 fifth-graders divided into two groups, the control group and the experiment group. The control group was taught regular English lessons. The experiment group learned simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…His study revealed that pre-pubescent EFL students can acquire a native-like English pronunciation by watching cartoons and overcoming all mispronunciation obstacles that occur with many foreign English learners. In another study, Nhung and Dieu (2020), examined the EFL learners' communicative skills improvement with the help of cartoons as a teaching tool. It was found that in six weeks the target group, for which the English cartoons were incorporated into their English lessons, has shown much greater improvement in listening and speaking skills than the control group that had lessons without them.…”
Section: Literature Review Literature Reviewmentioning
confidence: 99%
“…His study revealed that pre-pubescent EFL students can acquire a native-like English pronunciation by watching cartoons and overcoming all mispronunciation obstacles that occur with many foreign English learners. In another study, Nhung and Dieu (2020), examined the EFL learners' communicative skills improvement with the help of cartoons as a teaching tool. It was found that in six weeks the target group, for which the English cartoons were incorporated into their English lessons, has shown much greater improvement in listening and speaking skills than the control group that had lessons without them.…”
Section: Literature Review Literature Reviewmentioning
confidence: 99%
“…Poštić (2015) concluded that children who were exposed to English cartoons at an early age performed better in their pronunciation and communication skills than other children who were not. In Vietnam, students who watched cartoons outside the classroom outperformed students who did not in speaking and listening skills (Le & Tran, 2020). One of the reasons is that cartoon watching is regarded as a beneficial practice for young learners of English since it enhances their language abilities and motivates them to study the language.…”
Section: Watching English Cartoonsmentioning
confidence: 99%